Are grouse populations unstable at the southern end of their range? - Cattadori, Isabella M.; Hudson, P. J. (country:DK, 2000)
The long-term temporal dynamics of four grouse species in the Italian Alps have been investigated in the attempt to reveal if the populations exhibit the tendency to cycle at the southern edge of their European range. Hunting statistics or count data were collected as total number of individuals shot or counted each year from five provinces. For the province of Trento data were available at the level of mountain groups and a more detailed investigation was carried out. The results from Trento were compared with the more general findings from the other four Italian provinces. Time series analysis was performed to investigate the pattern of cycle and autoregressive models were used to describe the density dependence structure. In general, the populations showed a weak or no tendency to regular fluctuations: rock ptarmigan Lagopus mutus and black grouse Tetrao tetrix populations exhibited the highest tendency to cycle with periods of 5-9 years while capercaillie Tetrao urogallus never showed regular fluctuations. Hazel grouse Bonasa bonasia cyclic dynamics were restricted to a few populations of Trento. When time series from Trento were corrected for hunting effort the detection of cycle among populations sharply increased but no differences in the strength of second order density dependence or in the period length was observed. Alinear first order autoregressive model explained better the intrinsic structure of the majority of populations. We compare the findings with studies conducted on populations of northern Europe and suggest possible reasons for the reduced tendency to cycle in the grouse populations of the Italian Alps